Examining the structure of images in the sonnets of the return period - Mostafa Mirdar Rezaei; Farzad Baloo (مطالعات زبانی و بلاغی)
The general judgments regarding the quality of the poetry in the return period are general and hypothetical, and their proof needs more and more detailed investigations. The structure of the poetic image is a collection of various rhetorical materials that resulted by the special vision and language of each poet; In other words, the result of analyzing the geometry of a poetic image will be various art structures that have played a role in the formation of that structure. One of the necessary tools for a thorough examination is the knowledge of stylistics, which, with its two characteristics of frequency and analogy, is a good criterion for examining the poetry of poets of any period. The current research, which is written in a quantitative-statistical way and with a stylistic approach and by examining the geometry of the images of the sonnets of six prominent poets of the return period (Mushtaq Esfahani, Hatef Esfahani, Azar Bigdeli, Soroush Esfahani, Sabai Kashani and Fethullah Khan Shibani), tries to avoid common generalizations regarding the similarity of the poetry of the poets of the period of return to the poetry of the poets of the previous styles, by presenting accurate statistics and It is clear about the amount of use of individual and combined artistic structures by each poet, apart from determining the level and quality of the structure of the images in terms of simplicity or complexity, by comparing the geometry of the images of the sonnets of the poets of this literary school with the structure of the images of the Iraqi and Indian style poets. The results of this research show that as we move away from the Indian style (and the Safavi era) and get closer to the Qajar period, the number of composite artworks and the percentage of complexity of the images decrease and the scale of individual artworks and images decreases. It is simply added; For example, the structure of Mushtaq's lyrical images (the first and closest poet of this research to the Indian style) is different from the geometry of other poets' lyrical images of this movement and is placed in the same line as the structure of Iraqi style images, but the structure of lyrical images Shibani's poems are much simpler than the structure of the images of other poets of this movement, as well as Iraqi and Indian poets.